Downy Brome (Bromus tectorum) Vernalization: Variation and Genetic Controls. Issue 3 (8th February 2018) - Lawrence, Nevin C.; Hauvermale, Amber L.; Burke, Ian C.
Abstract: Downy brome ( Bromus tectorum L.) is a widely distributed invasive winter annual grass across western North America. Bromus tectorum phenology can vary considerably among populations, and those differences are considered adaptively significant. A consensus hypothesis in the literature attributes the majority of observed differences in B. tectorum phenology to differing vernalization requirements among populations. A series of greenhouse experiments were conducted to identify differences in B. tectorum vernalization requirements and link vernalization to expression of annual false-brome [ Brachypodium distachyon (L.) P. Beauv.]-derived vernalization gene homolog ( BdVRN1 ). Results from this study indicate that variation in time to flowering is partially governed by differing vernalization requirements and that flowering is linked to the expression of BdVRN1 .